1999
DOI: 10.1093/oxfordjournals.jbchem.a022494
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Monooxygenase of Rhodococcus rhodochrous: Sequencing of the Grenomic DNA, and Hyperexpression, Purification, and Characterization of the Recombinant Enzyme

Abstract: Steroid monooxygenase of Rhodococcus rhodochrous is a Baeyer-Villigerase catalyzing the insertion of an oxygen atom between the C(17)- and C(20)-carbons of progesterone to produce testosterone acetate. The 5.1-kbp-long BamHI DNA fragment containing the steroid monooxygenase gene, smo, was cloned from the chromosomal DNA and sequenced. The smo gene is 1,650 nucleotides long, starts with a TTG codon, and ends with a TGA codon. The deduced amino acid sequence indicates that the enzyme protein consist of 549 amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…BP2 and Rhodococcus sp. strains Phi1 and Phi2 steroid monooxygenase from Rhodococcus rhodochrous (38), and an alkane monooxygenase of P. fluorescens DSM 50106 (31). In addition to these characterized BVMOs, the putative cyclohexanone monooxygenase from Rhodococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…BP2 and Rhodococcus sp. strains Phi1 and Phi2 steroid monooxygenase from Rhodococcus rhodochrous (38), and an alkane monooxygenase of P. fluorescens DSM 50106 (31). In addition to these characterized BVMOs, the putative cyclohexanone monooxygenase from Rhodococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning, Expression, and Purification-The gene coding for STMO from R. rhodochrous (8) was cloned into a Champion TM pET-vector (Invitrogen) for overexpression in Escherichia coli. The resulting protein contained a N-terminal His 6 -tagged SUMO, which can be removed by SUMO protease.…”
Section: Methodsmentioning
confidence: 99%
“…In 1999, steroid monooxygenase (STMO) from Rhodococcus rhodochrous was the second BVMO for which the gene was cloned and used for heterologous expression (8). However, so far no subsequent studies on this bacterial steroid degrading monooxygenase have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence comparison using the BLASTX program against the nonredundant GenBank database showed that the two Brevibacterium cyclohexanone monooxygenases are part of the large family of flavin-dependent monooxygenases. Sequences with the highest similarity are the Acinetobacter cyclohexanone monooxygenase (A28550) and the Rhodococcus steroid monooxygenase (AB010439) (3,24). The activities of both proteins have been characterized biochemically.…”
Section: Figmentioning
confidence: 99%